Comparison of early versus delayed timing of left ventricular assist device implantation as a bridge-to-transplantation: An analysis of the UNOS dataset. (15th January 2016) - Kitada, Shuichi; Christian Schulze, P.; Jin, Zhezhen; Clerkin, Kevin J.; Homma, Shunichi; Mancini, Donna M.
Abstract: Background: Placement of left ventricular assist devices (LVAD) as a bridge-to-heart transplantation (HTx) has rapidly expanded due to organ donor shortage. However, the timing of LVAD implantation is variable and it remains unclear if earlier implantation improves survival. Methods: We analyzed 14, 187 adult candidates from the United Network of Organ Sharing database. Patients were classified by 3 treatment strategies including patients medically treated alone (MED, n = 11, 009), patients on LVAD support at listing (Early-LVAD, n = 1588) and patients undergoing LVAD placement while awaiting HTx (Delayed-LVAD, n = 1590). Likelihood of HTx and event-free survival were assessed in patients subcategorized by clinical strategies and UNOS status at listing. Results: The device support strategy, despite the timing of placement, was not associated with increased likelihood of HTx compared to MED group. However, both LVAD implantation strategies showed better survival compared to MED group (Early-LVAD: HR 0.811 and 0.633, 95% CI 0.668–0.984 and 0.507–0.789, for 1A and 1B; p = 0.034 and p < 0.001, Delayed-LVAD: HR 0.553 and 0.696, 95% CI 0.415–0.736 and 0.571–0.847, for 1A and 1B; both p < 0.001, respectively). Furthermore, there was no significant difference in survival between these LVAD implantation strategies in patients listed as 1B (p = 0.500), although Early-LVAD implantation showed worse survival in patients listed as 1A (HR 1.467, 95% CI 1.076–2.000; p = 0.015). Conclusion: LVAD support strategies offer a safe bridge-to-HTx. Those candidates who receive urgent upfront LVAD implantation for HTx, and improve to 1B status, would achieve competitive survival with those who receive elective LVAD implantation.